2019
DOI: 10.1016/j.ijdevneu.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal, paternal, and neonatal risk factors for neural tube defects: A systematic review and meta‐analysis

Abstract: Objective Neural tube defects [NTDs] are severe congenital anomalies. The etiology of NTDs is not fully known, and studies on the potential risk factors of NTDs present inconsistent results. Thus, we conducted a systematic review and meta‐analysis to investigate the maternal, paternal, and neonatal risk factors for NTDs. Study design We systematically reviewed relative original studies published through October 6, 2018 available in Pubmed, Embase and the Cochrane Library without restrictions for language. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 75 publications
(116 reference statements)
1
17
0
1
Order By: Relevance
“…NTDs are caused by the interaction of environmental and genetic factors. The environmental factors include medicine exposure, infection, and radiation ( Jia et al, 2019 ). Valproic acid (VPA) is one of the most commonly prescribed drugs to control epileptic seizures.…”
Section: Introductionmentioning
confidence: 99%
“…NTDs are caused by the interaction of environmental and genetic factors. The environmental factors include medicine exposure, infection, and radiation ( Jia et al, 2019 ). Valproic acid (VPA) is one of the most commonly prescribed drugs to control epileptic seizures.…”
Section: Introductionmentioning
confidence: 99%
“…The PRISMA flow diagram 30 in Figure 1 shows that we identified 4,004 articles and screened 3,592 abstracts. Of the 661 articles that underwent full‐text screening, 592 were ineligible and 22 were removed as they reported only associations covered by more comprehensive or Cochrane Reviews (see Table ), resulting in 47 reviews being included 12,31‐76 . Six eligible reviews were identified through citation tracking, 77‐82 resulting in a final sample of 53 reviews.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3 shows moderate‐certainty evidence that paternal age of ≥40 years is associated with a greater risk of miscarriage, and low‐certainty evidence that paternal age of 35–39 years may not be associated with greater or reduced risk of this outcome 42 . Low‐certainty evidence was found that paternal age of <20 years is associated with an increased risk of spina bifida, 51 that maternal age of ≥35 years is associated with a greater risk of urinary incontinence, 36 and that maternal age of ≥45 years is associated with increased risk of: an abnormal five‐minute Apgar score, foetal loss, pregnancy complications and caesarean delivery, relative to maternal age of <45 years 52 . Low‐certainty evidence was also found that interpregnancy intervals shorter than 6 months are associated with an increased risk of low weight, small‐for‐gestational‐age and preterm births, and that interpregnancy intervals of ≥60 months are also associated with an increased risk of these outcomes 38 .…”
Section: Resultsmentioning
confidence: 99%
“…el las variables sociodemográficas se encontró baja escolaridad (5 años o menos) de padres tuvo una relación significativa con la incidencia de anomalías congénitas. Datos similares han arrojado otros estudios en los que se encontró una asociación entre la baja escolaridad materna y el desarrollo de defectos del tubo neural (OR: 1,42; IC95%: 1,19-1,70) 13 .…”
Section: Discussionunclassified